Big Data Analytics Skills for Future Accountants - Donny Maha Putra; Rufina Aribarahmani (Riset Akuntansi dan Keuangan Indonesia, 2025)
Big data analytics technology has changed the landscape of the labour market, including in the field of accounting. This study examines the influence of hard and soft skills of big data analytics on three dimensions of employability: human capital, individual attributes, and career development in accounting students. The method used was quantitative, with a questionnaire survey on 286 accounting students, which was analyzed using Structural Equation Modeling (SEM) through SmartPLS 4.0. Hypothesis tests were carried out to determine the influence of hard skills and soft skills on each dimension of employability. The study results show that hard and soft skills have a positive and significant effect on human capital and career development. However, only soft skills have a significant effect on individual attributes, while hard skills do not show a significant effect on this dimension. These results support the theory of job market signalling, in which technical and non-technical skills serve as signals for employers. The originality of this research lies in testing the combination of hard skills and soft skills of big data analytics in the context of accounting student employability, which has not been widely discussed before.